Epidemiological characteristics of child injury in a tertiary paediatric surgical centre in Bangladesh - Chowdhury, Tanvir Kabir; Sadia, Ayesha; Khan, Rumana; Farjana, Abida; Sharmin, Efat; Hasan, Kafil; Rini, Fatima Farhana; Farooq, Md Abdullah Al (Asian Journal of Medical and Biological Research, 2020)
While high income countries (HICs) have reduced the mortality from child injury, it is increasing in the low- and middle-income countries (LMICs). However, injury registry and reporting are inconsistent and not well developed in the LMICs. This study aims at describing the epidemiology of child injury in a tertiary paediatric surgical centre in Bangladesh. We retrospectively analysed all patients of injury between 0 and 12 years of age admitted in the Department of Paediatric Surgery, Chattogram Medical College Hospital during January 2017 to June 2020. Analysis was done for the hospital prevalence, age and sex distribution, seasonal variations, mechanism of injury, site of involvement, and mortality from injury. There were a total of 538 patients and male to female ratio was 2.01:1. Hospital prevalence was 6.71%. Mean age was 6.60 ± 3.32 years. School age children were affected more (51.7%); and “6-10 years” age group had the highest number injuries (251 patients, 46.65%). The most common mechanisms of injuries were road-traffic accident (RTA, 35.32%), followed by fall (26.39%) and „stab or cut injury‟ (20.63%). Males experienced more abdominal injuries and females had more perineal injuries (P=0.00). RTA was the commonest mechanism in males (37.05%) and falls were the commonest mechanism in females (32.96%). „Stab or cut injury‟ was the commonest mechanism in infants and toddlers, and RTA was commonest among pre-school and school age children. There were no significant seasonal variations (P=0.09). There were 5.76% intentional injuries. Mortality was 2.60% and major causes of mortality were RTA and animal assaults. Injuries were more prevalent during the mid-childhood with an overall increasing trend with age. Mechanism of injury and site of involvement were different among different age groups and between sexes. Asian J. Med. Biol. Res. September 2020, 6(3): 577-586